'Do It Yourself' and 'digital fabrication' for new way of founding life. Issue 3 (November 2020) - Parisi, N
Abstract: In architecture, 'Do It Your Self' has always been a prerogative of those who need to build a home or a place dedicated to a life necessity with few resources. Even today, as in the past, self-construction is applied in very poor contexts and is implemented using traditional techniques and technologies. Today, however, the new dimension of Digital Fabrication offers a completely new scenario in architecture, including the world of 'Do It Your Self'. Machines and robots can enhance the possibilities available to those who want to get involved in it. Several companies innovate production processes by connecting the construction traditions of the past with new digital technologies. Young communities in search of self-determination feel the need to be personally involved in the regeneration and foundation of their living environment. Thus, the designer becomes a technical process consultant in the production and an animator of the community that builds its own architecture. Through four examples applied in the four editions of the International Summer Academy 'Self Made Architecture', the FabLab team of the Polytechnic University of Bari proposes a new approach to lead the new urban and peri-urban communities to found again their own places of life. The latest experimentation concerns the fourth edition still in the planning phase focused on the application of additive printing in architecture through the use of a mixture of raw earth. This technological advancement can represent a major resource to root the 'Do It Yourself' approach in the processes of Self-determination of local communities. This project results from the collaboration of the FabLab Poliba group with the development and research department of WASP, an Italian leading company in 3D printing, and from the scientific collaboration between the Polytechnic University of Bari and the Faculty of Architecture of Damascus.